1976
DOI: 10.1155/apec.3.77
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conduction by Percolation in Thick Film Resistors

Abstract: Thick film resistors are widely used in microelectronic devices, however the mechanism of electrical conduction in these resistors has not yet been fully understood. In particular the anomalous behaviour of the temperature coefficient of resistance (T.C.R.) vs. temperature for a purely ohmic resistor has not been explained. The anomaly is that the T.C.R. is negative at low temperatures, is zero around room temperature and becomes positive at higher temperatures. This paper demonstrates that the electrical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Moreover, it is demonstrated that the resulting picture fits the framework of a recently proposed model 3 6 even though only unconvincing explanations were proposed up to now. Figure 2 shows how the experimental measurements satisfactorily fit the proposed equation in a wide temperature range.…”
Section: Introductionsupporting
confidence: 51%
“…Moreover, it is demonstrated that the resulting picture fits the framework of a recently proposed model 3 6 even though only unconvincing explanations were proposed up to now. Figure 2 shows how the experimental measurements satisfactorily fit the proposed equation in a wide temperature range.…”
Section: Introductionsupporting
confidence: 51%
“…This is because firing temperature helps in healing some of the crystal defects formed during the high pressure pressing process in the moulder and also firing the resistor helps in burning -out any resin type materials left in the resistor itself (Forlani and Prudenziati, 1998). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These cermets films like any other thin film resistors (TFRs) are not homogeneous but consist of small particles of Cromium in the matrix of SiO 2 ( Forlani and Prudenziati, 1976). Cermets structured resistors, like TFRs based on Bi 2 Ru 2 O 7 , exhibit a high stability and very low Temperature Coefficient of Resistance (TCR) (Avadhanu andKshirsagar, 2007, Forlani andPrudenziati, 1998). Screen printing and firing onto a substrate is a method used for producing (TFRS).…”
Section: Introductionmentioning
confidence: 99%
“…Hill and Forlani and Prudenziati 2 have shown that electrical conduction in thick-film resistors can be explained using the concepts of electron percolation and hopping between conductive sites, and a model has been proposed for the temperature dependence of resistivity (p(T)), 3 ---exp (1) in which 3 is a constant and To is the activation temperature. Both are dependent on the density (N) of conductive sites and the decay constant (a) for the electron wavefunction in the resistor glaze.…”
Section: Conduction Theorymentioning
confidence: 99%